Exploring nursing and allied health perspectives of quality oral care after stroke: A qualitative study. (August 2020) - Ferguson, Caleb; George, Ajesh; Villarosa, Amy R; Kong, Ariana C; Bhole, Sameer; Ajwani, Shilpi
Background: Maintaining good oral health remains a challenge among those hospitalised after stroke. Stroke nurses and allied health clinicians have a potential role in providing oral care, but no studies in Australia to date have explored their perceptions and needs. Aims: To explore the perspectives of nursing and allied health stroke clinicians regarding oral care for stroke patients across acute care and stroke rehabilitation settings. Methods: This study followed an exploratory qualitative design, using a constructivist approach. Participants from two metropolitan public hospitals were purposively recruited to participate in focus groups. Data was thematically analysed. Results: Twenty-one clinicians participated. Clinicians' knowledge and practices relating to oral healthcare for stroke patients were inadequate. Most staff felt they did not have adequate knowledge, resources and training to administer oral care in this setting and proposed enhancing education of stroke clinicians, patients and informal caregivers, as well as improving quality point of care resources. There was overall support for the integrated dental care after stroke model of care. Discussion: This study revealed many gaps in current care and highlighted areas for improvement. Patients and their caregivers needed to be actively engaged as partners to improve oral healthcare within acute and rehabilitation stroke settings. Conclusion: This study provided insight into nurses' and allied health stroke clinicians' current knowledge and practices of oral care in various stroke settings. The findings from this study will inform development of a model of care to train stroke nurses in providing oral care.